Effect of the Dielectric and Mechanical Properties of the Polymer Matrix on ZnO‐Nanowire‐Based Composite Nanogenerators Performance. Issue 9 (13th August 2020) - Doumit, Nicole; Poulin‐Vittrant, Guylaine
Abstract: The effect of Young's modulus and dielectric permittivity of the polymer matrix in vertically integrated nanogenerators (VING) on their output performance is studied by combining the finite element method and analytical modeling. To conduct this study, an elementary cell is considered, based on one ZnO nanowire (NW) surrounded by the polymer matrix. It is demonstrated that the polymer matrix should have the lowest Young's modulus and permittivity as possible, in order to maximize the output voltage and power. Four different materials, which have already been proposed in literature for such composite VING, are then compared: Parylene C, poly(methyl methacrylate), Al2 O3, and poly(dimethylsiloxane) (PDMS). Simulation results show that PDMS, which has the lowest values of both Young's modulus and permittivity, gives the highest output performance. Finally, the sensitivity to another design parameter—the surface density of the NWs—is calculated, and it is shown that choosing a polymer material with the lowest Young's modulus and permittivity is more powerful to improve the VING performance. Abstract : The effect of Young's modulus and dielectric permittivity of the polymer matrix in vertically integrated nanogenerators (VING) on their output performance is studied by combining the finite element method and analytical modeling. It is shown that choosing a polymer material with the lowest Young's modulus and permittivity is more powerful to increase the VING performance.